2017
DOI: 10.1002/2016jd025812
|View full text |Cite
|
Sign up to set email alerts
|

Improved scheme for Cross‐track Infrared Sounder geolocation assessment and optimization

Abstract: An improved scheme for Cross‐track Infrared Sounder (CrIS) geolocation assessment for all scan angles (from −48.5° to 48.5°) is developed in this study. The method uses spatially collocated radiance measurements from the Visible Infrared Imaging Radiometer Suite (VIIRS) image band I5 to evaluate the geolocation performance of the CrIS Sensor Data Records (SDR) by taking advantage of its high spatial resolution (375 m at nadir) and accurate geolocation. The basic idea is to perturb CrIS line‐of‐sight vectors al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Compared with results without the geolocation correction, the STDs for all scenes are reduced by 18%, 38%, 39%, and 38% for M13, M15, M16, and I5, respectively, but there is little change in the radiance biases. From the last column in Figure , the STD for all scenes without the uniformity test is 0.27 K for I5, which is comparable to the results from Figure 15 in Wang, Zhang, et al (). This result indicates that the simplified correction method used in this study is able to mitigate the geolocation errors identified by Wang, Zhang, et al ().…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Compared with results without the geolocation correction, the STDs for all scenes are reduced by 18%, 38%, 39%, and 38% for M13, M15, M16, and I5, respectively, but there is little change in the radiance biases. From the last column in Figure , the STD for all scenes without the uniformity test is 0.27 K for I5, which is comparable to the results from Figure 15 in Wang, Zhang, et al (). This result indicates that the simplified correction method used in this study is able to mitigate the geolocation errors identified by Wang, Zhang, et al ().…”
Section: Discussionsupporting
confidence: 82%
“…The geolocation correction is important for VIIRS/CrIS intercomparisons (Tobin et al, ; Wang, Zhang, et al, ). As mentioned, the results presented in Figure are after the simplified geolocation error correction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations